Aircraft measurement campaign on summer cloud microphysical properties over the Tibetan Plateau - Chang, Yi; Guo, Xueliang; Tang, Jie; Lu, Guangxian (Scientific reports, 2019)
We reported the first aircraft campaign on summer cloud microphysical properties conducted in July of 2014 over the Tibetan Plateau during the third Tibetan Plateau Atmospheric Sciences Experiment (TIPEX-III), and demonstrated that the summer clouds over the Tibetan Plateau were primarily characterized as mixed-phase cumulus clouds induced by strong solar radiation heating. Moreover, the characteristic number concentration of cloud droplets (2~50 μm in diameter) in developing cumuli was around 10 cm −3 , which was about 1~2 orders of magnitudes lower than other continent and ocean regions, and that for large drops (>50 μm in diameter) was around 10 −3 cm −3 , which was also lower than other regions. The droplet spectrum distributions (DSDs) of cloud drops were much wider than other regions, indicating that the cumulus clouds over the plateau could form precipitation easier than that in other regions. Ice microphysics was characterized as very active glaciation and riming processes with high supercooled water content, which caused the formation of high concentration of graupel particles in clouds. The findings of this study suggest that these unique cloud microphysical properties formed by the high topography and clean environment of the Tibetan Plateau could induce higher precipitation efficiency when airflow passed over the plateau, so that the plateau could act as a regional “water tower”.